Edukasi Pencegahan Diabetes dan Pemanfaatan Bahan Alam sebagai Antidiabetes bagi Masyarakat Pengunjung Car Free Day Colomadu, Karanganyar - Sujono, Tanti Azizah; Kusumowati, Ika Trisharyanti Dian; Munawaroh, Rima; Utami, Wahyu; Sari, Asti Arum; Nurwaini, Setyo; Isnaniyah, Dhevi Zahra Latifatul; Anindya, Talitha Ahnaf; Firdaus, Farhand Ahmad; Harindasari, Amorita Azzah; Balqis, Moetia Rahman; Anjati, Yasinta Widia (Universitas Muhammadiyah Surakarta, 2025)
Diabetes mellitus (DM) is a chronic (non-communicable) disease whose prevalence is currently increasing. Public awareness of the importance of early detection and prevention of diabetes is still relatively low, because this disease is sometimes asymptomatic. Various efforts to prevent and treat DM continue to be developed, including through public education. This activity aims to increase public knowledge about diabetes and the use of natural ingredients as antidiabetics. Car-free day Colomadu was chosen as a strategic location to reach the community by providing accessible health education. This activity is a collaboration between the UMS Faculty of Pharmacy and the Aisyiyah Colomadu Branch Management. The method used is to detect diabetes through blood sugar level checks and education about diabetes, which is done by providing leaflets. The level of knowledge is measured by comparing the pretest and posttest. A total of 19 respondents met the inclusion criteria: visitors to the Colomadu car-free day, had had a blood sugar level check, were willing to fill out a questionnaire, and had a history of education/work not in the health sector. Based on the results of statistical tests, there was a significant increase in knowledge about diabetes (p<0.001) with a pretest value (72.11) in the sufficient category and a posttest value (78.95) in the good category. Based on this, education using this leaflet can increase public knowledge about diabetes. Still, it is recommended that other educational methods, such as counseling accompanied by questions and answers, be used to optimize the results.